2022
DOI: 10.1126/scitranslmed.abq4130
|View full text |Cite
|
Sign up to set email alerts
|

Durable protection against the SARS-CoV-2 Omicron variant is induced by an adjuvanted subunit vaccine

Abstract: Despite the remarkable efficacy of COVID-19 vaccines, waning immunity and the emergence of SARS-CoV-2 variants such as Omicron represents a global health challenge. Here, we present data from a study in nonhuman primates demonstrating durable protection against the Omicron BA.1 variant induced by a subunit SARS-CoV-2 vaccine comprising the receptor binding domain of the ancestral strain (RBD-Wu) on the I53-50 nanoparticle adjuvanted with AS03, which was recently authorized for use in individuals 18 years or ol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 48 publications
6
36
0
Order By: Relevance
“…Further, we observed improved potency in naïve animals by formulating IVX-411 with MF59, an oil-in-water emulsion. Such results have been externally replicated for I53-50-based SARS-CoV-2 vaccines in naïve human patients [38,[41][42][43]. Our results are immunogenically similar to those observed from other RBD-based, single-component, SARS-…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Further, we observed improved potency in naïve animals by formulating IVX-411 with MF59, an oil-in-water emulsion. Such results have been externally replicated for I53-50-based SARS-CoV-2 vaccines in naïve human patients [38,[41][42][43]. Our results are immunogenically similar to those observed from other RBD-based, single-component, SARS-…”
Section: Discussionsupporting
confidence: 82%
“…Further, we observed improved potency in naïve animals by formulating IVX-411 with MF59, an oil-in-water emulsion. Such results have been externally replicated for I53-50-based SARS-CoV-2 vaccines in naïve human patients [38,4143]. Our results are immunogenically similar to those observed from other RBD-based, single-component, SARS-CoV-2 VLP vaccines, which use nanoparticles such as ferritin [44,45], hepatitis B surface antigen [46], or mi3 (a variant of the I3-01 VLP) [4750], as well as biochemical conjugation methods such as SpyCatcher and sortase [45,47].…”
Section: Discussionmentioning
confidence: 82%
“…We compared neutralizing antibody responses elicited following vaccination of BALB/c mice with three distinct AddaVax-adjuvanted protein subunit immunogens. Mice were immunized at weeks 0 and 3 with a clinical-stage, multivalent RBD-nanoparticle (RBD-NP) (Arunachalam et al, 2021;Walls et al, 2020aWalls et al, , 2021Arunachalam et al, 2022;Song et al, 2022), an S ''2P'' prefusion-stabilized S (Pallesen et al, 2017;Walls et al, 2020a), or a next-generation prefusion-stabilized HexaPro S (Hsieh et al, 2020;Walls et al, 2021). Sera were collected 2, 5, and 8 weeks post-prime, and serum neutralizing activity (expressed as the dilution inhibiting 50% of entry: ID 50 ) was evaluated using single-round vesicular stomatitis virus (VSV) Report ll pseudotyped with G614 S, Beta S (B.1.351: L18F, D80A, D215G, L242-L244 deletion, R246I, K417N, E484K, N501Y, D614G, A701V), or Gamma S (P.1: L18F, T20N, P26S, D138Y, R190S, K417T, E484K, N501Y, D614G, H655Y, T1027, V1176F) in two distinct cell lines (VeroE6/TMPRSS2 [Lempp et al, 2021] and HEK293T/human ACE2 [Crawford et al, 2020]).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there is uncertainty whether vaccines matching dominant circulating SARS-CoV-2 variants such as those used for seasonal influenza are needed, or if the repeated use of Wuhan-Hu-1–based vaccines will suffice. Recent work showed that boosting previously immunized macaques with Beta or Omicron mRNA S vaccines or with Beta RBD nanoparticle vaccines elicited comparably high titers of antibodies broadly neutralizing multiple variants relative to Wuhan-Hu-1–based vaccines ( 59 61 ). Furthermore, administration of Wuhan-Hu-1–based vaccine boosters in humans was shown to elicit appreciable titers of neutralizing antibodies and prevent severe disease associated with Omicron infections ( 11 , 19 , 62 65 ).…”
Section: Discussionmentioning
confidence: 99%